The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ece3.3551
|View full text |Cite
|
Sign up to set email alerts
|

Taking movement data to new depths: Inferring prey availability and patch profitability from seabird foraging behavior

Abstract: Detailed information acquired using tracking technology has the potential to provide accurate pictures of the types of movements and behaviors performed by animals. To date, such data have not been widely exploited to provide inferred information about the foraging habitat. We collected data using multiple sensors (GPS, time depth recorders, and accelerometers) from two species of diving seabirds, razorbills (Alca torda, N = 5, from Fair Isle, UK) and common guillemots (Uria aalge, N = 2 from Fair Isle and N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 100 publications
(171 reference statements)
1
23
0
Order By: Relevance
“…Further, it has been well demonstrated that the bottom time of a dive is positively related to the rate of prey encounters for elephant seals foraging in open ocean systems 26,5052 . This has also been observed in a range of other diving predators 5356 . More specifically, hunting time, as defined by reduced vertical movement rates, has recently been validated as the foraging index associated with the highest number of prey capture attempts for the types of summarised dive profiles we use in this study 57,58 .…”
Section: Seals Reveal the Distribution And Abundance Of Mesopelagic Psupporting
confidence: 66%
“…Further, it has been well demonstrated that the bottom time of a dive is positively related to the rate of prey encounters for elephant seals foraging in open ocean systems 26,5052 . This has also been observed in a range of other diving predators 5356 . More specifically, hunting time, as defined by reduced vertical movement rates, has recently been validated as the foraging index associated with the highest number of prey capture attempts for the types of summarised dive profiles we use in this study 57,58 .…”
Section: Seals Reveal the Distribution And Abundance Of Mesopelagic Psupporting
confidence: 66%
“…Modeled krill distributions have also been used to better understand spatial and temporal aspects of their patchiness (Dorman et al, 2015;Messie and Chavez, 2017). The feeding data for tagged blue and fin whales presented here can offer further insight into the distribution and scale of prey patches across southern and central California waters, similar to how seabird foraging tracks have been used to infer prey availability and patch quality in other areas (Chimienti et al, 2017). Since direct observations of prey abundance were not available for this study, linking blue and fin whale feeding bouts to modeled krill distribution could be an additional step to both validate krill models and tie the overserved whale behavior more directly to prey abundance.…”
Section: Discussionmentioning
confidence: 94%
“…1 kg) and play a key role in the energy flow through circumpolar marine food webs in temperate and sub-Arctic waters (Gaston and Jones, 1998;Montevecchi, 2000;de L Brooke, 2004). Owing to small wings that reduce underwater drag, they are the deepest diving bird that can fly (250 m; Chimienti et al, 2017) with lower than expected metabolic costs during diving but higher than expected flight costs (Elliott et al, 2013). Emerging insights into the physiological processes during diving, involving reductions in blood flow to metabolically expensive organs (Niizuma et al, 2007) and reductions in core temperature and heart rate (Wilson et al, 1992;Elliott et al, 2013) suggest the metabolic costs of diving for murres may be lower than previously predicted, and possibly even decrease with depth which may allow them to extend their aerobic dive limit (Gerlinsky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%